Salud bucal de las escolares de la institución Santa María Goretti municipio de Caldas (Antioquia), 1999 - Magda Beltrán S.; Blanca Susana Ramírez P.; Dora María Gutiérrez G.; Leslie Andrea Jocame M.; John Santiago Urrego A.; Nancy Amparo Areiza M.; Paola Rocío Hernández T. (Universidad de Antioquia, 2001)
A transversal descriptive study was carried out in a sample of 176 girls randomly selected from an institution where the College of Dentistry of the University of Antioquia has been doing preventive and oral health care activities for several years. The average number of decayed, missing, filled deciduos teeth (dmft) due to dental caries was estimated; the same condition was determined for the permanent dentition, also, a survey was answered by the mother or guardian of the school child. The purpose of the study was to collect information regarding history and prevalence of dental caries, oral hygiene, and treatment needs, this would later serve as a base to reorient the oral health activities that are carried out at the school. The average age of the study group was 8 years, a caries prevalence of 51.1% was found and the dmft was 2.3. (CI 95%, 1.99- 2.69) the average plaque index was 1.3 (CI 95%, 1.22- 1.38). In the dmft and DMFT indexes, the caries component had a higher percentage (45% and 75% respectively) which indicates the need to change the oral health activities of the population studied in order to avoid a more severe morbidity that will eventually result in higher costs.